The Role of the Regional Development Planning Agency in the Preparation of the Medan City Medium Term Development Plan - Muhammad Anshari Hutasuhut; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
The purpose of this research is to identify and describe the role of the Regional Development Planning Agency in the preparation of the mid-term development plan for the city of Medan. and to find out how the preparation of the RPJMD for the city of Medan. This research is located at BAPPEDA PEMKO MEDAN. This research uses descriptive research. Sources of data collection carried out with primary data and secondary data through in-depth interviews with the head of BAPPED. As well as using data collection methods through observation and documentation. BAPPEDA is a supporting element of the mayor, which is led by a head of the Agency which is located under and responsible to the mayor of Medan, BAPPEDA has the task of carrying out the preparation and implementation of regional policies in the field of urban development planning. The Regional Medium Term Development Plan (RPJMD) is one part of development planning. After the inauguration of the new Mayor of Medan with a new vision and mission, a new RPJMD was drawn up. And in the preparation of the RPJMD, it is an elaboration of the vision and mission of the Regional Head. As well as in the preparation of the RPJMD, the most important coordination is with BAPPEDA. The results of this study indicate that the role of BAPPEDA in the preparation of the Medan City RPJMD is as follows: Harmonizing the schedule for implementing agency activities, integrating similar and related activities, evaluating planning and providing guidance in guidance.